Waking up muscle stem cells: PI3K signalling is ringing. (26th March 2018) - Relaix, Frederic; Machado, Léo
Abstract : Adult skeletal muscle injury instructs endogenous quiescent stem cells to activate for repair. The pathways involved in this activation remain poorly understood. An elegant study by Wang et al (2018 ) combine mouse molecular genetics with muscle regeneration experiments, cell culture and transcriptomic analysis to show that early activation depends on a PI3K‐mTORC1‐Jun/FoxOs signalling axis. Abstract : Mouse genetics combined with cell culture and transcriptome analyses highlight dependence of satellite cell activation on PI3K–mTORC1–Jun signalling.